Wireless Ad Hoc and Sensor Networks A Cross-Layer Design Perspective - Jurdak, Raja.; SpringerLink (Online service) (Boston, MA : Springer US, 2007)
Wireless Ad Hoc and Sensor Networks: A Cross-Layer Design Perspective deals with the emerging design trend that transcends traditional communication layers for performance gains in ad hoc and sensor networks. The author explores the current state of the art in cross-layer approaches for ad hoc and sensor networks, providing a comprehensive design resource. The book offers a structured comparison and analysis of both layered and cross-layer design, providing readers with an overview of the many issues relating to ad hoc and sensor networks. The benefits of these cross-layer approaches are examined through three diverse case studies: a monitoring sensor network using Radio Frequency waves, an ad hoc network that uses Ultra Wide Band Radio, and an acoustic underwater sensor network for environmental monitoring. Wireless Ad Hoc and Sensor Networks: A Cross-Layer Design Perspective is interdisciplinary in character, and should be of value to software engineers, hardware engineers, application developers, network protocol designers, graduate students, communication engineers, systems engineers, and university professors.
Ad Hoc and Sensor Networks: Opportunities and Challenges -- Ad Hoc and Sensor Networks: Opportunities and Challenges -- Layered Communication Approaches -- Physical Layer -- Data Link Layer -- Network Layer -- Transport and Middleware Layers -- Application Layer -- Cross-Layer Approaches -- Cross-Layer Design -- Cross-Layer Architectures -- Applied Cross-Layer Approaches -- Case Studies -- Optimization of an RF Sensor Network -- UWB Ad Hoc Network -- Acoustic Underwater Sensor Network -- Concluding Remarks and Future Directions.
Keywords: Engineering; Computer software -- Reusability; Computer communication systems; Computers; Computer simulation; Electrical engineering; Engineering; Communications Engineering, Networks; Computer Communication Networks; Performance and Reliability; Information Systems and Communication Service; Simulation and Modeling; Signal, Image and Speech Processing; Electronic books